2021
DOI: 10.3389/fmicb.2021.650771
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Salinity Stress in Peanut by Application of Endophytic Bacteria

Abstract: The development of salinity affects 7% of the world’s land surface, acting as a major constraint to crop productivity. This study attempted to use the co-evolving endophytes of peanut to alleviate salinity stress and enhance the yield of peanut. Diverse and different tissue colonizing endophytes were isolated from peanut and screened in vitro by seed germination bioassay imposing gradients of salinity, with two cultivars TG37A (susceptible) and GG2 (moderately resistant), in potted conditions using saline irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 71 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…The occurrence of Bacillus tequilensis was also reported in other ecological niches like 2000‐years old shaft tomb (Gatson et al, 2006), mangrove soil (Sharifi & Kunchirman, 2021), saline water pond (Cortés‐Camargo et al, 2021), geothermal hot spring (Fachrial et al, 2020), soil crust (Zhao et al, 2019), coastal soil (Pathak et al, 2014), fermented goat milk (Abid et al, 2019), fermented soybean (Chaurasia et al, 2020), Thai milk kefir (Vijitra et al, 2018) and chicken gastrointestinal tract (Rani et al, 2017). The use of this strain as an inoculant is also reported on limited occasions (Kang et al, 2019; Pal et al, 2021; Zhou et al, 2021). Another opportunistic endophyte, B. kochii reported in the present work was first isolated from dairy and pharmaceutical production sites (Seiler et al, 2012) and later reported from soil (Liu et al, 2020), compost pit, coral reef, insect gut (Wan et al, 2017), fermented fish (Alvionita et al, 2020) and sparingly found as endophytes in tomato seed (Someya et al, 2021), papaya (Thomas et al, 2019) and noni (Liu et al, 2015b).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The occurrence of Bacillus tequilensis was also reported in other ecological niches like 2000‐years old shaft tomb (Gatson et al, 2006), mangrove soil (Sharifi & Kunchirman, 2021), saline water pond (Cortés‐Camargo et al, 2021), geothermal hot spring (Fachrial et al, 2020), soil crust (Zhao et al, 2019), coastal soil (Pathak et al, 2014), fermented goat milk (Abid et al, 2019), fermented soybean (Chaurasia et al, 2020), Thai milk kefir (Vijitra et al, 2018) and chicken gastrointestinal tract (Rani et al, 2017). The use of this strain as an inoculant is also reported on limited occasions (Kang et al, 2019; Pal et al, 2021; Zhou et al, 2021). Another opportunistic endophyte, B. kochii reported in the present work was first isolated from dairy and pharmaceutical production sites (Seiler et al, 2012) and later reported from soil (Liu et al, 2020), compost pit, coral reef, insect gut (Wan et al, 2017), fermented fish (Alvionita et al, 2020) and sparingly found as endophytes in tomato seed (Someya et al, 2021), papaya (Thomas et al, 2019) and noni (Liu et al, 2015b).…”
Section: Discussionmentioning
confidence: 93%
“…To validate our hypothesis, the ecological niches of these endophytes, as reported earlier, were correlated with our data. Bacillus endophyticus was first reported as an endophyte of the cotton plant (Reva et al, 2002) and later found as an endophyte of several plants, including sugarcane (Pirhadi et al, 2018), cotton (Vinodkumar et al, 2018), onion (Ibrahim et al, 2020), mung bean, cowpea and soybean nodules (Bakhtiyarifar et al, 2021), Chinese mountain legumes (Pang et al, 2021), groundnut (Pal et al, 2021), medicinal plants like Salvadora persica (Moustafa et al, 2016), Vernonia anthelmintica (Rustamova et al, 2020), Gloriosa superba (Das et al, 2021) and halophyte Salicornia europaea (Zhao et al, 2016). This species was also isolated from wheat rhizosphere (Ibarra‐Villarreal et al, 2021; Verma et al, 2016), sugarcane rhizosphere (Mukhtar et al, 2017), rice phyllosphere (Devarajan Arun et al, 2020), termatorium soil (Chauhan et al, 2016), and honeydew of cotton whitefly (Roopa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The salinity-induced harmful impact on plant development can be ascribed to specific ion toxicity, osmotic stress, nutritional disturbance, or combinations of these factors ( Parida and Das, 2005 ; Ju et al, 2021 ). Studies have inoculated endophytic bacteria to alleviate SS within numerous plant species ( Pal et al, 2021 ; Sofy et al, 2021 ). In this study, E. ludwigii B30 inoculation enhanced plant development in non-SS and SS conditions, which was manifested by higher shoot height, root length, shoot and root biomass (DW and FW) ( Table 1 ) and TQ ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that endophytic PGPB with the ability to directly promote plant growth are successful in helping plants to overcome salt stress (a major environmental/abiotic stress worldwide). These reported studies of overcoming salt stress have included tomato [ 47 ]; sorghum, cucumber, and tomato [ 48 ]; chickpea [ 49 ]; and peanut [ 50 ]. Moreover, the approach of using endophytic PGPB to overcome abiotic stress has been very recently reviewed [ 51 , 52 ].…”
Section: Plant Bacterial Endophytesmentioning
confidence: 99%